Understanding the Seepage Behavior of Nai Gaj Dam through Numerical Analysis - Bashir, A.; Chaudhry, R.; Qureshi, A. L.; Memon, U.; Bheel, N. (Engineering, Technology & Applied Science Research, 2022)
This study presents the seepage patterns of earth-fill dams, using critical situations by employing the finite element approach. The Nai Gaj dam is 65km northwest of Dadu city in Sindh Province, Pakistan. In this study, the seepage through the main dam body and foundation is computed and simulated for different scenarios, i.e. maximum, normal, and minimum reservoir level. Seepage analysis was conducted by using the SEEP/W sub-program of GEO-SLOPE software. Dam design parameters and dam geometry data were used as input data to compute the unknown seepage. The seepage behavior of the Nai Gaj dam is shown in terms of net flow which consists of equipotential lines, streamlines, velocity vectors, and phreatic lines. The results show the seepage flux, maximum seepage, and exit gradient at different reservoir levels. The results show that the average flow rate at normal, maximum, and minimum reservoir levels are 1.49×10-7cumec/m, 3.38×10-7cumec/m, and 2.108×10-8cumec/m respectively. In addition, the overall stability of the side slope of the dam is discussed.